1979
DOI: 10.1159/000181719
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Intolerance in Chronic Uremic Patients

Abstract: The metabolic effects of an acute acetate load have been investigated in chronic uremic patients and in controls. The decay rate of blood acetate levels was significantly lower in patients than in controls. Higher levels of blood acetoacetate and 2-oxoglutarate and plasma triglycerides were observed in the patients after the load. No difference was detectable in plasma levels of unesterified fatty acids and cholesterol between the two groups of subjects. Acetate oxidation in citric acid cycle may be reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Acetate is metabolized by the liver and skeletal muscles, yielding one mole of bicarbonate for each mole of acetate, but in chronic uremic patients acetate metabolism is impaired (1) and acetate contained in dialysis solutions can cause cardiovascular instability (8). Although the benefits of BHD over acetate dialysis remain controversial (9), several studies have shown beneficial effects of BHD in reducing the morbidity associated with dialysis (2,3), and BHD is currently the mainstay of dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetate is metabolized by the liver and skeletal muscles, yielding one mole of bicarbonate for each mole of acetate, but in chronic uremic patients acetate metabolism is impaired (1) and acetate contained in dialysis solutions can cause cardiovascular instability (8). Although the benefits of BHD over acetate dialysis remain controversial (9), several studies have shown beneficial effects of BHD in reducing the morbidity associated with dialysis (2,3), and BHD is currently the mainstay of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic uremic patients, acetate metabolism is impaired (1) and acetate present in dialysis solutions can cause cardiovascular instability. The benefits of bicarbonate hemodialysis (BHD) over acetate dialysis include a lower incidence of intra‐dialysis hypotension (2) and less post‐dialysis malaise (3), but bicarbonate dialysate also contains small amounts of acetate, which in vitro studies suggest may be harmful in some sensitive patients (3).…”
mentioning
confidence: 99%
“…However, even small amounts of acetate can induce nitric oxide production in vascular endothelial cells (2) and myocardial cells (3), leading to vasodilatation and reduced myocardial contractility, which might, in turn, cause intradialytic hypotension. Therefore, acetate‐free dialysate is expected to contribute to the maintenance of hemodynamic stability during hemodialysis (HD) sessions (4). In addition, acetate induces the expression of pro‐inflammatory cytokines in monocytes and polymorphonuclear neutrophil leukocytes, which may be responsible for chronic inflammation in HD patients (5).…”
mentioning
confidence: 99%
“…In these stable patients who had few problems using the standard acetate bath, improvement with a replacement dialysis solution of any son would have been difficult if not impossible to demonstrate. Thus, further trials of the acetate+lactate dialysis solution specifically in those pa tient groups who are intolerant to acetate [17] are indi cated.…”
Section: Discussionmentioning
confidence: 99%